Evaluation of Factors Influencing the Dispensing of Refill Medications at the Fourth-Floor Outpatient Pharmacy, Hamad Hospital, Qatar: A Retrospective Observational Study - Yousif, Abdelmonem B.; Darweesh, Rana Z M; Hamsa, Hasna Ameer; Alanzi, Amal Alhar; Saleh, Rowda Mohamed; Areqi, Abdullah Ahmed (University of Science and Technology, Yemen, 2025)
Background: Refilling prescriptions at outpatient pharmacies is an important part of managing chronic illnesses since it has a big effect on patient safety, following prescription regimens, and the efficiency of the healthcare system. Because there are so many patients and the prescriptions are so complicated. Objective: The study aims to evaluate three primary factors influencing the dispensing of refill medications: inaccuracies in prescription entry by physicians and chemists, the effects of altered appointment dates, and inconsistencies between sanctioned refill quantities and appointment schedules. Methods: Retrospective observational research encompassing 13,500 adult patients with active refill authorizations was executed from January to March 2025. The information came from the outpatient pharmacy on the fourth floor of Qatar's Hamad Hospital. Descriptive and inferential statistics, like t-tests and chi-square tests, were used to look into error rates and how they connect to demographic and prescription-related factors. Results: According to our investigation, the most common mistake was mismatched appointments and refill amounts (37.8%), followed by changes to appointment dates (25.9%) and inaccuracies in physician input (17.3%). Pharmacists made 12.3% of the mistakes, and doctors and pharmacists together made 6.7% of the mistakes. General medicine had the most mistakes (67.3% for mismatches and 63.8% for appointment changes), while pulmonary departments had the most chemistry mistakes (60.0%). Conclusion: Most of the time, mistakes in giving medications happen because of changes in the schedule, checking prescriptions, and conflicts in the schedule.